Targeting Lipooligosaccharide (LOS) for a Gonococcal Vaccine - Gulati, Sunita; Shaughnessy, Jutamas; Ram, Sanjay; Rice, Peter A. (Frontiers in Immunology, 2019)
The increasing incidence of gonorrhea worldwide and the global spread of multidrug-resistant strains of Neisseria gonorrhoeae, constitute a public health emergency. With dwindling antibiotic treatment options, there is an urgent need to develop safe and effective vaccines. Gonococcal lipooligosaccharides (LOSs) are potential vaccine candidates because they are densely represented on the bacterial surface and are readily accessible as targets of adaptive immunity. Less well-understood is whether LOSs evoke protective immune responses. Although gonococcal LOS-derived oligosaccharides (OSs) are major immune targets, often they undergo phase variation, a feature that seemingly makes LOS less desirable as a vaccine candidate. However, the identification of a gonococcal LOS-derived OS epitope, called 2C7, that is: (i) a broadly expressed gonococcal antigenic target in human infection; (ii) a virulence determinant, that is maintained by the gonococcus and (iii) a critical requirement for gonococcal colonization in the experimental setting, circumvents its limitation as a potential vaccine candidate imposed by phase variation. Difficulties in purifying structurally intact OSs from LOSs led to “conversion” of the 2C7 epitope into a peptide mimic that elicited cross-reactive IgG anti-OS antibodies that also possess complement-dependent bactericidal activity against gonococci. Mice immunized with the 2C7 peptide mimic clear vaginal colonization more rapidly and reduce gonococcal burdens. 2C7 vaccine satisfies criteria that are desirable in a gonococcal vaccine candidate: broad representation of the antigenic target, service as a virulence determinant that is also critical for organism survival in vivo and elicitation of broadly cross-reactive IgG bactericidal antibodies when used as an immunogen.